African Americans are less likely to enroll in preclinical Alzheimer's disease clinical trials. Issue 1 (14th October 2016) - Zhou, Yan; Elashoff, David; Kremen, Sarah; Teng, Edmond; Karlawish, Jason; Grill, Joshua D.
Abstract: Introduction: Alzheimer's disease (AD) incidence is disproportionately high in African Americans, yet, recruitment of this community to AD clinical trials is challenging. Methods: We compared 47 African Americans and 78 whites in their willingness to enroll in a hypothetical preclinical AD trial and examined barriers and facilitators in their decision making. Results: African American race (OR = 0.45; 95% CI, 0.22–0.93) and score on the research attitude questionnaire (OR = 1.12; 95% CI, 1.04–1.22) were independently associated with willingness to participate. African Americans rated study risks, the requirement of a study partner, study procedures, the ratio of drug to placebo, and study location as more important factors in the decision whether to enroll than did whites. Discussion: These results suggest that researchers will encounter challenges in recruiting African Americans to preclinical AD trials. Future research will be necessary to understand the optimal means to improve recruitment of underrepresented populations.